Description of three new species of frog–biting midges (Diptera: Corethrellidae) from the Central Brazilian Amazon - Jessica Feijó Almeida (Consortium of European Natural History Museums, 2021)
Three species of Corethrella Coquillett, 1902 from the state of Amazonas, Brazil are described as new to science based on female adult specimens. Corethrella cabocla Feijó, Belchior, Marialva & Pessoa sp. nov. possesses four large setae on the frons between the ventromedial area of ommatidia, a wide clypeus with 1–4 setae, a wing with the apex of R2 basal to the apex of M2 and with a midlength band, and with the abdomen entirely dark brown. Corethrella ielemdei Feijó, Ramires, Lima & Pessoa sp. nov. possesses an elongated coronal suture, four large setae on the frons between the ventromedial area of ommatidia, a clypeus squarish with 42–43 setae, a wing with the apex of R2 basal to the apex of M1 and with a midlength band and dark scales on the basal and subbasal areas of the anterior margin, legs with dark scales, and with the abdomen entirely dark brown. Corethrella menini Feijó, Picelli, Ríos-Velásquez & Pessoa sp. nov. possesses wings with the apex of R2 basal to the apex of M2 and a midlength band, with darker basal scales along all veins, basal band dark scales on C, Sc, R, M, and Cu and the abdomen entirely dark brown. With the addition of the new species, the numbers of frog-biting midges described in the Amazon basin, Brazil and in Neotropical region are now 31, 49 and 80 species, respectively.